Service staff encounters with dysfunctional customer behavior: Does supervisor support mitigate negative emotions? - Xiao, Biyan; Liang, Cuijing; Liu, Yitong; Zheng, Xiaojing (Frontiers in Psychology, 2022)
Dysfunctional customer behavior is common in service settings. For frontline employees, negative encounters can cause short-term despondency or have profound, long-term psychological effects that often result in both direct and indirect costs to service firms. Existing research has explored the influence of dysfunctional customer behavior on employee emotions, but it has not fully investigated the psychological mechanism through which customer misbehavior transforms into employee responses. To maintain service quality and employee well-being, it is important to understand the impact of customer misconduct on employee emotions and its effect on subsequent service behavior. To assess the process through which dysfunctional customer behavior manifests as negative emotions in frontline service employees, and the influence of negative employee emotions on their prosocial service behavior, we surveyed 185 frontline banking service employees. We sought information on service employee experiences, attitudes, and feelings regarding dysfunctional customer behaviors, the perceived level of supervisor support, and employee prosocial service behavior intentions. Structural equation modeling and hierarchical linear modeling were used for statistical analysis and hypothesis verification. Results indicate that dysfunctional customer behavior has a positive relationship with bank service employee negative emotions and a negative influence on employee prosocial service behavior. The study found that negative emotions fully mediated the relationship between dysfunctional customer behavior and prosocial service behavior. The moderating role that perceived supervisor support plays on the relationships between dysfunctional customer behavior and negative emotion was also investigated. The results show that perceived supervisor support moderates the relationship between dysfunctional customer behavior and negative employee emotions. Finally, the study provides bank managers with effective strategies to assist frontline employees to manage and deter dysfunctional customer behavior, and presents employees with internal recovery strategies when encountering dysfunctional customer behavior.